[Rezension von: Brueggemann, Walter, 1933-, Disruptive grace] - Moberly, Walter (The journal of theological studies, 2012)
Walter Brueggemann is fortunate in his friends and editors. As in previous years some of his essays were collected and edited by Patrick Miller, so here addresses given to a variety of ecclesial audiences from 2002 to 2009 have been put together and introduced by Carolyn Sharp, an up-and-coming Old Testament scholar at Yale., There are seventeen addresses in all, arranged in four sections. Part I, ‘Torah’, contains ‘Summons to a Dialogic Life’, ‘Exodus: Limit and Possibility’, ‘Sabbath as Antidote to Anxiety’, and ‘The Countercommands of Sinai’. Part II, ‘Prophets’, contains ‘Every City a Holy City: The Holy City in Jeopardy’, ‘Every City a Holy City: The City of Possibility’, ‘Prophetic Ministry in the National Security State’, and ‘The Land Mourns’.